Exploring 5-MeO-DMT as a pharmacological model for deconstructed consciousness - Timmermann, Christopher; Sanders, James W; Reydellet, David; Barba, Tommaso; Luan, Lisa X; Angona, Óscar Soto; Ona, Genís; Allocca, Giancarlo; Smith, Carl H; Daily, Zachary G; Mason, Natasha L; Kloft-Heller, Lilian; et al. (Neuroscience of consciousness, 2025)
5-MeO-DMT is a short-acting psychedelic that is anecdotally reported to induce a radical disruption of the self and a paradoxical quality of aroused, waking awareness that is nevertheless devoid of any specific perceptual contents. Here, we conducted an exploratory observational study of the phenomenological and neuronal effects of this compound. We collected micro-phenomenological interviews, psychometric questionnaires, and electroencephalography (EEG) in naturalistic ceremonial settings where 5-MeO-DMT was ingested. Results revealed that the 5-MeO-DMT experience followed a dynamic progression that-only in the most extreme cases-manifested as a complete absence of self-experience and other phenomenal content with preserved awareness. Furthermore, visual imagery, bodily self-disruption, narrative self-disruption, and reduced phenomenal distinctions occurred in a variable fashion. EEG analyses revealed the 5-MeO-DMT experience was characterised by (global) alpha and (posterior) beta power reductions, implying a mode of brain functioning where top-down models are inhibited. Our preliminary phenomenological findings confirm the potential utility of 5-MeO-DMT as a pharmacological model for deconstructed consciousness while noting the limitations of employing retrospective questionnaires for this purpose. Considering the exploratory nature of this study and its limitations inherent to its naturalistic nature, further research employing real-time experience sampling and phenomenologically trained participants in controlled environments could expand our findings to meaningfully inform the potential of this tool for the scientific study of consciousness.
Keywords: serotonin; awareness; neurophenomenology; psychedelic; EEG; self